Re-thinking School Leadership and Management during COVID-19 in Pakistan - Bhamani, Shelina; Rehman, Muhammad Talha; Sturges, Marion (Journal of Education and Educational Development, 2022)
Covid-19 presented several challenges to the global infrastructure and it has certainly changed systems in almost every walk of life. Recovery will most likely create a new normal and the aftermath of the pandemic will change us as a species (Gleiser, 2020). Many commentators believe that the pandemic has offered humankind a chance to rethink its ways of life. Uncertainty could catalyze positive action. Responsibility, among various other values, is being revisited because simple actions like shaking hands, not wearing masks, and crowding at community gatherings could expose all individuals to risk.
Keywords: Education; COVID; Governance; COVID-19; Mental Health; Well-being; Social development